PERAN KEARIFAN LOKAL DALAM MEMPERTAHANKAN KOHESI SOSIAL MASYARAKAT DESA SUKADANA, KECAMATAN CIOMAS, KABUPATEN SERANG, PROVINSI BANTEN - Kurniawan Jaki, Rifal; Saefudin Malik, Saefudin Malik; Joko Nasrullah, Joko Nasrallah; Salsabila Krisna Hermanto, Salsabila Krisna Hermanto; Eni Sutianingsih, Eni Sutianingsih; Windi Novianti, Windi Novianti; Selviyana Putri; Ryfa Camila Maharani; Bela Isma Fauziyah; Lilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Local wisdom is a cultural heritage consisting of values, norms, and social practices passed down from generation to generation as a guide for community life. Amid modernization, local wisdom plays an important role in maintaining social cohesion and strengthening community solidarity. This study aims to analyze the role of local wisdom in preserving social cohesion among communities in Ciomas District, Serang Regency, Banten Province. The study employed a qualitative approach using a descriptive method. The findings indicate that the community continues to preserve various forms of local wisdom, including mutual cooperation, social solidarity, social interaction, religious traditions, and local cultural practices. These values contribute to strengthening social relationships, enhancing social concern, and maintaining social harmony. The study concludes that local wisdom serves not only as a cultural heritage but also as social capital that plays a significant role in maintaining social integration and cohesion amid ongoing social change.